Audit Tenure Dan Auditor Rotation: Literature Review - Jati, Rani Arista (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The argument about audit tenure and auditor rotation revolves around efforts to maintain auditor independence and audit quality. There are two hypotheses that explain the effects arising from a long period of audit tenure. The auditor independence hypothesis states that a long auditor engagement period will reduce audit quality and financial reporting due to the appearance of disruption to auditor independence, while the hypothesis of expertise states that a longer engagement period can improve audit quality through the learning process. Nevertheless, the length of the auditor's engagement period should be long enough so that auditors can apply their competencies and expertise to the audit process and obtain an adequate understanding of the company and the environment they are auditing. Various countries have implemented mandatory auditor rotation and various studies have been conducted, yet the studies on auditor rotation's influence on audit quality show mixed results. Therefore, the author summarizes the results of these studies in order to provide an overview for auditors to always maintain their independence, as well as stakeholders for decision making and regulators for the development of regulations in the field of auditing.